(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Study this have destination for knowing about how much far understanding student school base about discipline self , sense of responsibility answer , as well Self leadership ? study this is also done for could test is Theory leadership this could brought to child Elementary School , with consideration pattern suitable delivery _ for done. The research we did this time use method approach direct to subject research . Results obtained is Theory this enough easy for understood by the subject research , though needed a little encouragement for in some point . It means Theory this could brought for Student school base , though in the end permanent needed adjustment style nature , and highly expected exists role accompaniment could by the environment closest subject .